2006
DOI: 10.1074/jbc.m602817200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Domains of Human Tryptophan Hydroxylase 2 (hTPH2)

Abstract: Tryptophan hydroxylase (TPH) is the rate-limiting enzyme in serotonin biosynthesis. A novel gene, termed TPH2, has recently been described. This gene is preferentially expressed in the central nervous system, while the original TPH1 is the peripheral gene. We have expressed human tryptophan hydroxylase 2 (hTPH2) and two deletion mutants (N⌬150 and N⌬150/ C⌬24) using isopropyl ␤-D-thiogalactopyranoside-free autoinduction in Escherichia coli. This expression system produced active wild type TPH2 with relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 46 publications
6
81
1
Order By: Relevance
“…Similar to the cell free system, all TPH2 variants appeared to be more soluble in HEK 293 cells than in E. coli: 73-83% of the total amount of TPH2 was observed in the supernatant fraction after centrifugation at 12,000 Â g for 10 min (data not shown), except for p.Arg303Trp which was mainly recovered in the insoluble fraction as shown previously . These solubility estimates are higher than previously reported for WT, p.Pro206-Ser, and p.Arg441His [Carkaci-Salli et al, 2006;Cichon et al, 2008;Winge et al, 2007]. The difference is explained by the use of a more effective cell lysis procedure and avoidance of repeated freeze/thaw cycles of the cells.…”
Section: Expression Of Tph2 Variants In Human Cellscontrasting
confidence: 51%
See 2 more Smart Citations
“…Similar to the cell free system, all TPH2 variants appeared to be more soluble in HEK 293 cells than in E. coli: 73-83% of the total amount of TPH2 was observed in the supernatant fraction after centrifugation at 12,000 Â g for 10 min (data not shown), except for p.Arg303Trp which was mainly recovered in the insoluble fraction as shown previously . These solubility estimates are higher than previously reported for WT, p.Pro206-Ser, and p.Arg441His [Carkaci-Salli et al, 2006;Cichon et al, 2008;Winge et al, 2007]. The difference is explained by the use of a more effective cell lysis procedure and avoidance of repeated freeze/thaw cycles of the cells.…”
Section: Expression Of Tph2 Variants In Human Cellscontrasting
confidence: 51%
“…2 and 3). It has been reported that the N-terminal domain of TPH2 is responsible for the lower solubility and stability of TPH2 in comparison to TH and PAH [Carkaci-Salli et al, 2006;Thorolfsson et al, 2002]. However, for all three enzymes, phosphorylation of serines in the N-terminal appears to stabilize the protein [Miranda et al, 2002;Moy and Tsai, 2004;Royo et al, 2005;Winge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The regulatory domains of other members of the family, such as TPH1 and TH, have been shown to modulate enzyme activity and thermostability through various mechanisms, including phosphorylation by protein kinases (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). In line with this, the extended N terminus of TPH2 contains a serine at position 19, which is a candidate for PKA phosphorylation (32) and has been recently shown to interact with 14-3-3 proteins in a phosphorylationdependent manner to increase protein stability (33).…”
mentioning
confidence: 74%
“…34 As the truncated TPH2-TR retains the entire regulatory domain and a small portion of catalytic domain (Figure 1a), its dominant-negative activity may lie in its interference with the normal function of the regulatory domain in the full-length protein. 35,36 A number of genetic analyses have indicated association between the TPH2 gene and central nervous system disorders like depression, 14 bipolar disorder 37,38 and attention-deficit/hyperactivity disorder. 39 A functional characterization was carried out for a rare loss-of-function R441H mutation in an elderly depression cohort whose patients experienced life-long depression, and were resistant to treatment.…”
Section: Discussionmentioning
confidence: 99%